Farmers’ Social Capital in Supporting the Sustainability of Bird’s Eye Chili Farming in Sukowiryo, Jelbuk District, Jember Regency - Rifa Anisatul Kumairoh; Sri Subekti; Sofia Sofia; Rokhani Rokhani (Agrisocionomics: Jurnal Sosial Ekonomi Pertanian, 2026)
Bird’s eye chili farming is an important part of the horticultural sector that plays a role in supporting food needs and the rural economy. This study aims to analyze farmers' social capital in bird’s eye chili farming in Sukowiryo Village, Jelbuk District, Jember Regency. This research uses a quasi qualitative method, with data collection techniques using in-depth interviews, passive participation observation, and documentation of the main and supporting informants. The results show that social capital, consisting of social networks, norms, and trust plays an important role in every stage of farming, starting from the procurement of seeds or seedlings, land processing, planting, maintenance, pest and disease control, harvest and post-harvest, to marketing. Social networks between farmers, families, labor, market actors, and formal institutions facilitate the flow of information and resources. Norms, both written and unwritten, serve as guidelines for cooperation. Trust built on shared experiences and common goals strengthens social cohesion and ensures the sustainability of cooperation. This research shows that social capital is not only a supporting factor, but a strategic resource in realizing the sustainability of bird’s eye chili farming. Therefore, strengthening social capital can improve farmers' welfare